Obtaining raised density connections by thermosonic microwelding in 3D integrated microcircuits - Lanin, V. L.; Petuhov, I. B. (Technology and design in electronic equipment, 2014)
The authors consider the processes of obtaining raised density microwelded connections in 3D-integrated microcircuits by the thermosonic microwelding. The processes include the use of the raised frequencies of ultrasound, application of the microinstrument with a thinning of the working end and precision devices for ball formation, which provide reproducibility of connections quality.At a small step of contact pads, the use of a wire of small diameter (not more than 25 µm) is necessary for devices with a multilevel arrangement of leads and chess arrangement of contact pads on the chip, providing the maximum length of the formed crosspieces does not exceed 4–5 mm.